Polyester fiber carbon black composite solar interface evaporator and preparation method and application thereof

CN121651472BActive Publication Date: 2026-10-13CNSIG JILANTAI CHLOR-ALKALI CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610156383.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-04
Publication Date
2026-10-13
Estimated Expiration
2046-02-04

AI Technical Summary

Technical Problem

[0007]针对现有技术中纤维基太阳能界面蒸发器在高盐度水体处理过程中存在的盐结晶严重、蒸发效率衰减快、长期稳定性不足、以及复杂结构导致成本高等问题,本发明提供一种结构简单、成本低廉、便于规模化制备且具有优异抗盐结晶性能的聚酯纤维/炭黑复合太阳能界面蒸发器及其制备方法和应用

Benefits of technology

[0020]与现有技术相比,本发明通过特定配比的沥青/炭黑复合光热层与网状聚酯纤维基底的结合,并采用将蒸发器设置于水面下特定深度的应用方式,实现了在高盐环境下优异的抗盐结晶与稳定蒸发性能,有效延缓了盐分析出,保证了长期运行的蒸发效率;该蒸发器结构简单、制备工艺便捷、所用原料成本低廉,具有良好的规模化生产前景;同时,利用沥青的粘结作用使光热层与纤维结合牢固,耐久性好,适应性强,可灵活应用于多种高盐废水处理场景,整体方案环境友好,为太阳能界面蒸发技术的实际应用提供了高效、经济且可靠的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121651472B_ABST
    Figure CN121651472B_ABST
Patent Text Reader

Abstract

The application discloses a polyester fiber carbon black composite solar interface evaporator and a preparation method and application thereof, and belongs to the technical field of solar energy utilization and seawater desalination. The evaporator takes a reticular polyester fiber fabric as a flexible substrate, and a photo-thermal composite layer composed of pitch and carbon black with a specific mass ratio (2.5:1-3.5:1) is loaded on the surface of the substrate through an impregnation method, wherein the total loading amount of the pitch and the carbon black is preferably 20%-70% of the mass of the substrate. The preparation method comprises the steps of preparing a pitch / carbon black dispersion liquid, impregnating the fabric and drying and curing. In application, the evaporator is placed on the liquid surface of high-salinity wastewater to be treated or at a depth of 0-2 cm below the liquid surface (preferably 0.5 cm below the water surface) for solar-driven evaporation. Through optimization of material composition, loading amount and working position, the application realizes the synergy of efficient photo-thermal conversion and effective inhibition of salt crystallization, has the advantages of high evaporation efficiency, good salt resistance, long-term working stability, simple preparation process, low cost and the like, and is particularly suitable for high-salinity wastewater concentration and solar seawater desalination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of solar energy utilization and seawater desalination / high-salt wastewater treatment, specifically to the preparation of an interfacial photothermal evaporator, and in particular to a solar interfacial evaporator constructed based on a polymer fiber and carbon black composite material and its application in solar-driven water evaporation and desalination. Background Technology

[0002] Freshwater scarcity has become a global problem, and seawater desalination is one of the important ways to solve it. Traditional seawater desalination technologies (such as multi-effect flash evaporation and reverse osmosis) generally suffer from high energy consumption, complex processes, and reliance on fossil fuels, which are detrimental to sustainable development. In recent years, solar-driven interfacial evaporation technology has received widespread attention due to its advantages such as directly utilizing solar energy to achieve water evaporation, being green and low-carbon, and having zero energy consumption.

[0003] This technology typically uses materials with photothermal conversion capabilities as the evaporation interface, converting light energy into heat energy under sunlight, causing the water at the interface to evaporate rapidly. A typical interface evaporator includes a photothermal layer, a water transport layer, and an insulation layer. Among these, the photothermal layer is the core for achieving efficient photothermal conversion, and its materials and structure directly affect the evaporation efficiency.

[0004] Fiber-based materials (such as natural fibers, synthetic fibers, and inorganic fibers) are widely used as substrates or functional layers in interfacial evaporators due to their advantages such as high specific surface area, good hydrophilicity, porous structure, flexibility, cutability, and low cost. For example, natural fibers such as cotton and linen have strong water conductivity, chemical fibers such as polyester (PET) and polypropylene (PP) are low-cost and resistant to chemical corrosion, and inorganic fibers such as carbon fiber and basalt fiber have good light absorption performance and high stability. By loading photothermal materials (such as carbon black, graphene, and metal compounds) onto the surface or inside of fibers, high-performance fiber-based solar interfacial evaporators can be prepared.

[0005] However, in practical applications, especially when treating high-salinity water (such as seawater and concentrated industrial brine), the rapid crystallization of salt at the evaporation interface becomes a critical challenge. Salt crystals cover the photothermal surface, reduce light absorption, and block steam overflow channels, leading to a sharp decline in evaporation efficiency and shortening the device's lifespan. Currently, various strategies have been developed to address the salt crystallization problem, mainly divided into active (such as water washing for desalination and regional crystallization salt collection) and passive (such as self-cleaning design, utilizing convection effects, directional fluid transport, and Janus structure design). However, these strategies still have certain limitations: active methods require human intervention and are difficult to automate continuously; in passive methods, designs such as Janus structures may sacrifice evaporation rates, and evaporators relying on natural convection or simple hydrophilic structures still face the risk of salt crystallization when treating near-saturated high-salinity wastewater.

[0006] Furthermore, the photothermal conversion efficiency, long-term stability, cost-effectiveness, and overall performance under high-salt environments of existing fiber-based evaporators still need further improvement. In particular, developing an evaporator structure that is simple to manufacture, low in cost, has stable photothermal performance, and can effectively inhibit salt crystallization or facilitate salt management under high-salt conditions remains a technical problem that needs to be solved in this field. Summary of the Invention

[0007] To address the problems of severe salt crystallization, rapid evaporation efficiency decay, insufficient long-term stability, and high cost due to complex structure in existing fiber-based solar interface evaporators during high-salinity water treatment, this invention provides a polyester fiber / carbon black composite solar interface evaporator with simple structure, low cost, easy large-scale preparation, and excellent resistance to salt crystallization, as well as its preparation method and application.

[0008] Specifically, the present invention aims to solve at least one of the following technical problems: How to effectively inhibit or delay the formation of salt crystals at the evaporation interface while maintaining high evaporation efficiency; How to simplify the structural design and manufacturing process of evaporators, reduce production costs, and ensure a strong and durable bond between the photothermal functional layer and the substrate; How to provide a highly adaptable interfacial evaporation solution that can operate stably in water bodies with different salinity compositions and concentrations.

[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: First, a solar interface evaporator is provided, comprising: Flexible porous substrate, which is a mesh polyester fiber fabric; The photothermal conversion layer is composed of a composite of pitch and carbon black, and is uniformly loaded onto the fiber surface of the mesh polyester fiber fabric by means of the pitch as a binder, forming a firmly bonded coating. The mass ratio of the asphalt to the carbon black is (2.5:1) to (3.5:1). The total load of the asphalt and carbon black accounts for 10% to 95% of the mass of the mesh polyester fiber fabric.

[0010] Furthermore, the mass ratio of the asphalt to carbon black is preferably (2.8:1) to (3.2:1).

[0011] Furthermore, the total loading of the asphalt and carbon black is preferably 20% to 70%.

[0012] Furthermore, the pore size, thickness, and weight of the mesh polyester fiber fabric can be selected according to actual evaporation and water supply requirements.

[0013] Secondly, a method for preparing the above-mentioned solar interface evaporator is provided, including the following steps: S1. Preparation of dispersion: Mix asphalt and carbon black in a predetermined mass ratio, add to an organic solvent, and stir until a uniformly dispersed mixed solution is formed; S2. Impregnation: Immerse the mesh polyester fiber fabric in the dispersion solution and perform stirring impregnation treatment to ensure that the dispersion solution fully wets the fabric; S3. Drying: Remove the impregnated fabric and dry it to remove organic solvents and cure the asphalt, thereby forming a photothermal conversion layer on the fabric surface by fixing carbon black with asphalt.

[0014] Furthermore, steps S2 and S3 can be repeated once or multiple times to obtain higher asphalt and carbon black loadings.

[0015] Furthermore, the organic solvent is preferably dichloromethane.

[0016] Furthermore, the drying process is carried out at 50°C to 70°C.

[0017] Finally, the application methods of the above-mentioned solar interface evaporator are provided, including: The solar interface evaporator is placed at or below the surface of the water to be evaporated, and the evaporator is exposed to sunlight.

[0018] Furthermore, the solar interface evaporator is preferably located at a depth of 0.5 cm to 1 cm below the liquid surface.

[0019] Furthermore, the water to be evaporated is saline wastewater, including water containing Ca. 2+ Na + NO3 - CO3 2- SO4 2- OH - An aqueous solution containing one or more ions.

[0020] Compared with existing technologies, this invention achieves excellent anti-salt crystallization and stable evaporation performance in high-salt environments by combining a specific ratio of asphalt / carbon black composite photothermal layer with a mesh polyester fiber substrate and placing the evaporator at a specific depth below the water surface. This effectively delays salt precipitation and ensures long-term evaporation efficiency. The evaporator has a simple structure, convenient manufacturing process, and low raw material cost, showing good prospects for large-scale production. At the same time, the adhesive effect of asphalt ensures a strong bond between the photothermal layer and the fiber, resulting in good durability and strong adaptability. It can be flexibly applied to various high-salt wastewater treatment scenarios. The overall solution is environmentally friendly, providing an efficient, economical, and reliable solution for the practical application of solar interface evaporation technology. Attached Figure Description

[0021] Figure 1 The image shows the SEM morphology and absorption spectrum of material 9. Figure 2 The image shows the SEM morphology and absorption spectrum of material 1. Figure 3 The image shows the SEM morphology and absorption spectrum of material 2. Figure 4 The image shows the SEM morphology and absorption spectrum of material 3. Figure 5 The image shows the SEM morphology and absorption spectrum of material 4. Figure 6 The image shows the SEM morphology and absorption spectrum of material 5. Figure 7 The image shows the SEM morphology and absorption spectrum of material 6. Figure 8 The image shows the SEM morphology and absorption spectrum of material 7. Figure 9 These are photographs of the evaporator placed under different water level conditions during an evaporation experiment. Figure 10 The graph shows the change in evaporation rate during a 7-day stability test of the evaporator. Figure 11 This is a graph showing the instantaneous evaporation rate versus time during a continuous evaporation experiment of the evaporator for 10 hours. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0023] Examples 1-7: Preparation of composite photothermal evaporation materials (Materials 1-7) The core of this invention lies in providing a series of composite evaporation materials with different photothermal functional layer loadings. The following examples detail the methods for preparing materials 1-7 using a mesh polyester fiber fabric as a substrate, by controlling the concentrations of pitch and carbon black in the impregnation solution and the impregnation process. All examples used a commercially available mesh polyester fiber fabric (12 cm in diameter, 0.8 g in weight, and 2 mm mesh opening) as a uniform substrate, which was cleaned with ethanol and dried before use.

[0024] Example 1 (corresponding to material 1): 4 grams of bitumen were dissolved in 300 mL of dichloromethane and magnetically stirred until completely dissolved. Then, 1.25 grams of carbon black were added, and the mixture was stirred at high speed (1000 rpm) for at least 2 hours to form a uniform black dispersion. A polyester fiber fabric was immersed in this dispersion and slowly stirred at room temperature for 2 hours. The fabric was removed, excess liquid was drained, and the fabric was dried in a 60°C forced-air drying oven for 2 hours. The total mass of the resulting composite material was 0.8968 g. The calculated loading (the percentage of the total mass of bitumen and carbon black to the original fabric mass) was 12.1 wt.%.

[0025] Examples 2-4 (corresponding materials 2-4): The preparation method is the same as in Example 1, except that the initial feed amounts of asphalt and carbon black are changed to prepare materials with higher loading capacities. The specific feed ratios and results are as follows: Example 2 (Material 2): ​​10 g asphalt, 3.13 g carbon black. Total mass after drying: 0.9856 g, loading: 23.2 wt.%.

[0026] Example 3 (Material 3): 20 g asphalt, 6.25 g carbon black. Total mass after drying: 1.112 g, loading: 39.0 wt.%.

[0027] Example 4 (Material 4): 30 g asphalt, 9.37 g carbon black. Total mass after drying: 1.266 g, loading: 58.3 wt.%.

[0028] Example 5 (corresponding to material 5): Using the same dispersion (30 g pitch, 9.37 g carbon black, 300 mL dichloromethane) and initial impregnation-drying steps as in Example 4, a preliminarily loaded fabric was obtained. The fabric was then immersed again in the same dispersion for 5 minutes, removed, and dried again at 60°C. The total mass was 1.354 g, and the loading increased to 69.2 wt.%.

[0029] Example 6 (corresponding to material 6): The same dispersion as in Example 3 (20 g pitch, 6.25 g carbon black, 300 mL dichloromethane) was used. The polyester fabric was subjected to a cycle of "immersion for 2 hours - drying at 60°C" repeated 3 times. The final material had a total mass of 1.545 g and a loading of 93.1 wt.%.

[0030] Example 7 (corresponding to material 7): To investigate the effect of a single component, a comparative material containing only bitumen was prepared. 30 g of bitumen was dissolved in 300 mL of dichloromethane and stirred until dissolved. A polyester fiber fabric was immersed in this bitumen solution for 2 hours, then removed and dried at 60°C for 2 hours. The total mass was 1.154 g, with a loading of 44.3 wt.%. This material did not contain carbon black.

[0031] Example 8: Preparation of powder mixture (material 8) As another comparison, 3.2 g of pitch and 1.0 g of carbon black were placed together in an agate mortar, hand-ground and mixed evenly to obtain a physically mixed powder of pitch and carbon black, denoted as Material 8. This material is independent of the fiber carrier.

[0032] Example 9: Original substrate material (Material 9) Raw, untreated, 12 cm diameter, 0.8 g mass of untreated, virgin mesh polyester fabric was used directly and designated as Material 9.

[0033] The specific composition, raw material mass ratio, and calculated loading of the materials obtained in Examples 1-9 above are summarized in Table 1. Among them, the mass ratio of asphalt to carbon black in materials 1-6 and material 8 is consistently around 3.2:1, which is consistent with the preferred range of the present invention.

[0034] Table 1 Composition and proportions of each material Structural characterization and performance evaluation 1. Characterization of structural morphology and optical properties The material was characterized using scanning electron microscopy (SEM) and ultraviolet-visible-near-infrared absorption spectroscopy, and the results are as follows: Figure 1-8 As shown.

[0035] Figure 1 These are scanning electron microscope (SEM) images (left) and ultraviolet-visible-near-infrared (UV-Vis-NIR) absorption spectra of polyester fibers (material 9) (right). The SEM images show that the polyester fibers are bundled in the fabric, approximately 15 micrometers in diameter, with a smooth surface and uniform size. The UV-Vis-NIR absorption spectrum on the right shows that material 9 exhibits good absorption of UV-Vis light in the wavelength range of 200-750 nm.

[0036] Figure 2The images show the SEM morphology and absorption spectrum of Material 1. The left-hand scanning electron microscope image reveals micron-sized particles on the fiber surface, with some fibers agglomerated, indicating that the polyester fiber surface has been successfully loaded with the mixture of pitch and carbon black. The right-hand UV-Vis-NIR absorption spectrum shows good absorption in the 200-1400 nm wavelength range, indicating that the composite of pitch, carbon black, and polyester fiber has significantly enhanced UV-Vis-NIR light absorption compared to pure polyester fiber.

[0037] Figure 3 This is the SEM morphology and absorption spectrum of material 2. The scanning electron microscope image on the left shows that the amount of particulate matter on the surface of the polyester fiber is higher than that on the right. Figure 2 The increase is significant, which is due to the higher loading of material 2 compared to material 1. The UV-Vis-NIR absorption spectrum on the right side is... Figure 2 Similarly, this indicates that material 2 has a strong ability to absorb ultraviolet-visible-near-infrared light.

[0038] Figure 4 The image shows the SEM morphology and absorption spectrum of material 3. The scanning electron microscope image on the left shows that a large number of polyester fibers are bonded together, indicating that when the asphalt loading is too high, the asphalt firmly binds the carbon black particles and polyester fibers together, demonstrating the successful preparation of the polyester fiber-asphalt-carbon black composite material. The UV-Vis-NIR absorption spectrum on the right is still consistent with... Figure 2 Similarly, this indicates that material 3 also has a strong ability to absorb ultraviolet-visible-near-infrared light.

[0039] Figure 5 The images show the SEM morphology and absorption spectrum of Material 4. The scanning electron microscope image on the left shows that the polyester fiber surface is tightly coated with a layer of paste, which is likely the loaded asphalt and carbon black composite. The UV-Vis-NIR absorption spectrum on the right still shows good absorption in the 200-1400 nm wavelength range, but the absorption intensity in the near-infrared region is slightly enhanced compared to Material 3, indicating that increasing the loading of asphalt and carbon black is beneficial for enhancing light absorption efficiency.

[0040] Figure 6 The images show the SEM morphology and absorption spectrum of material 5. The scanning electron microscope image on the left shows a greater amount of pitch and carbon black composite material accumulated around the polyester fiber bundles, due to the further increase in loading. The UV-Vis-NIR absorption spectrum on the right still shows good absorption in the 200-1400 nm wavelength range, but the absorption intensity in the near-infrared region is significantly enhanced, further indicating that increasing the loading of pitch and carbon black is beneficial for enhancing light absorption efficiency.

[0041] Figure 7The images show the SEM morphology and absorption spectrum of material 6. The scanning electron microscope image on the left shows that the polyester fibers are almost entirely coated with the asphalt and carbon black composite. The UV-Vis-NIR absorption spectrum on the right still exhibits excellent light absorption in the wavelength range of 200-1400 nm.

[0042] Figure 8 The images show the SEM morphology and absorption spectrum of Material 7. The scanning electron microscope image on the left shows a large amount of particulate matter deposited on the surface of the polyester fiber, clearly different from Material 4. This is because Material 7 is only loaded with asphalt. This indicates that adding carbon black effectively enhances the adhesion between the asphalt and the polyester fiber. The UV-Vis-NIR absorption spectrum on the right still shows good light absorption in the wavelength range of 200-1400 nm. This indicates that the asphalt itself also has good near-infrared light absorption capabilities.

[0043] 2. Solar interface evaporation performance test A simulated solar evaporation test system was built, using a xenon lamp light source to simulate a standard solar radiation intensity (1 kW / m²). 2 Evaporation tests were conducted in petri dishes containing brine, and the evaporation rate was calculated by recording the system's mass loss using a high-precision electronic balance.

[0044] 2.1 Comparison of Evaporation Performance of Different Materials First, a blank experiment was conducted (without any materials), and the evaporation rate was measured to be 0.669 kg•m. -2 •h -1 Subsequently, the evaporation performance of materials 4, 7, 8, and 9 was tested, and the results are summarized in Table 2.

[0045] Table 2 Evaporation results of different materials Among them, material 4 (polyester / asphalt / carbon black ternary composite) exhibited the best performance, with an evaporation rate of 0.911 kg•m -2 •h -1 The improvement rate reached 36.3%.

[0046] Material 7 (polyester / asphalt binary composite) has an evaporation rate of 0.811 kg•m. -2 •h -1 The improvement rate was 21.2%, proving that the lack of carbon black led to a decrease in photothermal conversion efficiency.

[0047] The evaporation rate of material 8 (asphalt / carbon black powder) is only 0.770 kg•m. -2 •h -1 This indicates that if the photothermal material is simply floated on the water surface without a stable porous carrier structure, the photothermal material cannot function effectively.

[0048] Material 9 (original polyester fabric) has a certain degree of hydrophilicity and light absorption, resulting in an evaporation rate of 0.771 kg•m -2 •h -1 It is slightly higher than the blank, but far inferior to composite photothermal materials.

[0049] It is evident that the synergistic effect of the polyester fiber substrate, the asphalt binder, and the carbon black photothermal agent is the key to achieving efficient evaporation.

[0050] 2.2 Effect of Loading Rate on Evaporation Performance The evaporation performance of materials 1-6 under different loading rates was tested, and the results are shown in Table 3. The data shows that as the loading rate increases from 12.1% to 58.3%, the evaporation rate and efficiency increase increase simultaneously (materials 1 to 4). However, when the loading rate continues to increase to 69.2% and 93.1% (materials 5 and 6), the evaporation efficiency shows a decreasing trend. Combined with SEM morphology analysis, the optimal loading rate range is approximately 40%-70%. Within this range, the materials can ensure sufficient light absorption while maintaining the porous structure of the fabric to facilitate moisture transport and vapor escape. Excessive loading may lead to pore blockage, which is detrimental to evaporation.

[0051] Table 3 Evaporation results of materials with different loading capacities 2.3 Optimization of Evaporator Placement Depth To investigate the optimal working conditions, the material with the best performance, material 4, was placed at different depths in calcium-containing wastewater for testing. The results are shown in Table 4.

[0052] Table 4 shows the evaporation results of Material 4 placed at different water levels. When material 4 floats on the liquid surface (0 cm), the evaporation rate is 0.911 kg•m. -2 •h -1 .

[0053] When placed 0.5 cm below the liquid surface, the evaporation rate increases to a maximum of 0.957 kg·m³. -2 •h -1 The improvement rate reached 43.1%.

[0054] As the depth increased to 1 cm and 2 cm underwater, the evaporation rate gradually decreased.

[0055] This phenomenon indicates that moderate immersion (approximately 0.5 cm underwater) is the optimal choice. This depth ensures a continuous and sufficient supply of water to the heating zone through capillary action, while also utilizing slight convection beneath the liquid surface to promptly diffuse the salt ions enriched at the evaporation interface, thereby effectively inhibiting salt crystallization (as confirmed by post-experimental observation), while avoiding excessive heat loss caused by excessive immersion. Figure 9 The experiment setups at different placement depths are presented in a visually intuitive way.

[0056] 2.4 Adaptability to different salt solutions To verify the universality of the material, material 4 was placed 0.5 cm below the surface of different 0.2 mol / L salt solutions (CaCl2, NaNO3, Na2CO3, H2SO4, NaOH) for testing. The results are listed in Table 5.

[0057] Table 5. Evaporation results of Material 4 with different 0.2 mol / L salt solutions. Data shows that the evaporation rate increase remained stable between 38.2% and 46.4% in all test solutions. This fully demonstrates that the evaporator prepared in this invention has good adaptability and stable evaporation performance to various ion types and a wide pH range, making it suitable for treating complex high-salt wastewater.

[0058] 2.5 Long-term operational stability verification Stability is a core indicator for practical applications.

[0059] Cyclic stability: Material 4 was placed 0.5 cm below the surface of calcium-containing wastewater and exposed to light for 1 hour daily for 7 consecutive days. Figure 10 As shown, the daily evaporation rate remained stable with no significant decrease.

[0060] Continuous operating stability: Under the same conditions, material 4 was subjected to a single continuous 10-hour light exposure test. The evaporation rate decreased slightly with time. Figure 11 This indicates that as evaporation continues, the concentration of the salt solution increases, leading to a decrease in evaporation efficiency.

[0061] After the above tests were completed, the surface of material 4 was inspected, and no large amount of salt crystal accumulation or obvious coating peeling was found. This indicates that the evaporator of the present invention has excellent resistance to scale buildup and long-term operational reliability.

[0062] In summary, this invention provides a detailed, controllable fabrication method for a polyester fiber / carbon black composite solar interface evaporator through embodiments. By systematically adjusting the loading of the photothermal functional layer (preferably 40%-70%) and optimizing its operating position (preferably placed approximately 0.5 cm below the liquid surface), an evaporator exhibiting high-efficiency photothermal conversion, excellent resistance to salt crystallization, and long-term stability was successfully fabricated. This invention features a simple process and low-cost raw materials, providing a practical solution for solar-driven high-salinity wastewater concentration and seawater desalination.

[0063] The above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a polyester fiber / carbon black composite solar interface evaporator, characterized in that, Includes the following steps: (1) Mix asphalt and carbon black in a mass ratio of (2.5:1) to (3.5:1), add them to an organic solvent, and stir to disperse them to form a uniform dispersion; the organic solvent is dichloromethane; (2) The mesh polyester fiber fabric is immersed in the dispersion and stirred; the mesh size of the mesh polyester fiber fabric is 0.1 mm-20 mm. (3) Take out the impregnated fabric and dry it to obtain a composite evaporation material loaded with asphalt and carbon black; the drying is carried out at 50-70℃ for more than 2 hours; Steps (2) and (3) are repeated at least once to make the total load of pitch and carbon black reach 20%-70% of the mass of the polyester fiber fabric.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the asphalt to the carbon black is (2.8:1) - (3.2:1).

3. A polyester fiber / carbon black composite solar interface evaporator prepared by the method according to any one of claims 1-2, characterized in that, It comprises a continuous photothermal conversion layer consisting of a mesh polyester fiber fabric substrate and a composite material of pitch and carbon black uniformly loaded on its surface.

4. A method for interfacial evaporation using the solar interfacial evaporator of claim 3, characterized in that, The evaporator is placed at the surface of the saline wastewater or at a depth of 0-2 cm below the surface, and water evaporation is carried out under light.

5. The method according to claim 4, characterized in that, The evaporator is placed 0.5 cm below the water surface; the saline wastewater contains Ca. 2+ Na + NO3 - CO3 2- SO4 2- OH - High-salt wastewater containing one or more ions.

6. A solar interface evaporation system, characterized in that, include: (a) Light source; (b) Containers used to hold saline wastewater; (c) The solar interface evaporator of claim 3, which is disposed at the liquid surface or at a depth of 0-2 cm below the liquid surface in the container.

Citation Information

Patent Citations

  • Photo-thermal conversion film and preparation method and application thereof

    CN113790538A

  • Novel device for photothermal evaporation of sea water by solar energy

    WO2018196351A1